2019
DOI: 10.3389/fimmu.2019.02504
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical Stem Cell Transplantation in Children With Hematological Malignancies Using αβ+ T-Cell Receptor and CD19+ Cell Depleted Grafts: High CD56dim/CD56bright NK Cell Ratio Early Following Transplantation Is Associated With Lower Relapse Incidence and Better Outcome

Abstract: We prospectively analyzed outcomes of haploidentical hematopoietic stem cell transplantation using αβ+ T-cell receptor/CD19+ depleted grafts. Sixty-three transplantations were performed in 60 patients. Twenty-eight patients were diagnosed with acute lymphoblastic leukemia (ALL), 27 patients were diagnosed with acute myelogenous leukemia, and in eight other hematological malignancies were diagnosed. Twenty-three were in first complete remission (CR), 20 in second CR, 20 beyond second CR. Four patients developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Especially, a second haploidentical HSCT was associated with better relapse‐free survival in our cohort. Haploidentical HSCT has proven to be a highly efficient therapy especially for refractory malignant diseases 17‐20 . However, the small number of patients receiving a matched HSCT after blinatumomab does not enable a valid comparison between both HSCT subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, a second haploidentical HSCT was associated with better relapse‐free survival in our cohort. Haploidentical HSCT has proven to be a highly efficient therapy especially for refractory malignant diseases 17‐20 . However, the small number of patients receiving a matched HSCT after blinatumomab does not enable a valid comparison between both HSCT subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Immune reconstitution in children receiving TCRαβ + depleted haploidentical transplant was characterized by early and fast NK‐cell recovery constituting major lymphocyte subpopulation in the early phase following transplantation 52 . After conditioning, blood high level of interleukin‐15 provides a favorable environment not only for mature donor NK‐cell infused but also for NK cells maturing from engrafted hematopoietic stem cells.…”
Section: T‐cell Depletion In Haploidentical Transplantationmentioning
confidence: 99%
“…It has been previously reported using CD3 + CD19 + as TCD method that a high number of NK‐cells during early post‐transplant period protected form leukemia relapse 37 . Recently, the potential impact of CD56 dim and CD56 bright NK cells subpopulation on relapse incidence has been analyzed, resulting that the higher CD56 dim/ CD56 bright NK‐cell ratio the lower relapse incidence and better DFS 52 …”
Section: T‐cell Depletion In Haploidentical Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal analysis after allo‐HSCT showed that the incidence of aGvHD was associated with a delayed expansion of the CD56high subset 38 . In addition, a high CD56dim/CD56high NK cell ratio early after transplantation was associated with better disease‐free survival (DFS, 77% vs 28%; P = .001) due to lower relapse incidence (15% vs 37%; P = .04) in the αβ+ TCR/CD19+‐depleted graft model 39 . These results suggest that the number and subsets of NK cells affect transplantation prognosis.…”
Section: To Optimize Graft Composition By Graft Engineeringmentioning
confidence: 99%